Detection of HER2 through Antibody Immobilization Is Influenced by the Properties of the Magnetite Nanoparticle Coating - Villegas Serralta, Enrique; Zavala, Oscar; Flores Urquizo, Israel Alejandro; García Casillas, Perla E.; Chapa González, Christian (2018)
Considerable effort has been focused on improving the control of size, shape, and surface modifications to detect proteins. The purposeofthisstudywastocomparetheefficienciesofaminosilane-coatedmagnetite(As-M)nanoparticles(NPs),dextran-coated magnetitenanoparticles(Dx-M),andbarenanoparticlesforconjugatingsingle-chainvariablefragmentantibodies(scFvs)withthe aim of detecting the human epidermal growth factor receptor 2 (HER2) protein. Dx-M and As-M NPs were characterized using scanningelectronmicroscopy,energydispersiveX-rayspectroscopy,X-raydiffraction,andRamanspectroscopy.Dx-MandAs-M wereconjugatedwithamonoclonalscFvforactivetargetingoftheHER2antigen.AminosilanesurfacecoatingenhancedthescFv conjugationefficiencyovertwofoldcomparedtothatofthedextran-coatedmagnetiteNPsforthedetectionofHER2proteins.